Dziesięcioletnie leczenie rekombinowanym parathormonem niedoczynności przytarczyc u chłopca z częściowym zespołem Jacobsena - Dayal, Devi; Panigrahi, Inusha; Varma, Tandra; Gupta, Saniya; Gupta, Atul; Kumar, Rakesh; Sachdeva, Naresh (Pediatric Endocrinology Diabetes and Metabolism, 2021)
Pediatric hypoparathyroidism (HPT) is caused by inherited or acquired defects involving the synthesis or secretion of PTH, resistance to PTH action, or inappropriate regulation of PTH. Several syndromes such as DiGeorge syndrome, HDR (hypoparathyroidism, sensorineural deafness and renal dysplasia) syndrome, HRD (hypoparathyroidism, retardation, and dysmorphism) syndrome, Kenny-Caffey syndrome etc. may have associated HPT. In the present communication, we describe, the hitherto unreported, occurrence of HPT in a child with partial Jacobsen syndrome. Chromosomal Microarray analysis showed a heterozygous deletion of 4.7 Mb at cytoband 11q24.3q25 encompassing approximately 20 genes including JAM3 and NTM genes. The child was treated with recombinant human parathyroid hormone (rhPTH1-34) for 10 years. Throughout follow up, he required several adjustments in dosages of rhPTH1-34 and oral calcium to maintain serum calcium concentrations in low normal ranges. The bone turnover markers remained normal and oral calcium supplements were completely taken off after 8 years. In conclusion, our single-case experience indicates that long-term therapy of chronic HPT with rhPTH1-34 is safe and reduces the need for additional therapies